Constraints on competitive performance of attacker-defender dyads in team sports - Vilar, L.; Araújo, D.; Davids, K.; Travassos, B. (Journal of Sports Sciences, 2012)
Previous research on coordination dynamics of 1 vs. 1 sub-phases in team sports has reported stable emergent patterns of coordination in the displacement trajectories of attackers and defenders. The aim of this study was to use attacker-defender interactions in competitive team match-play to investigate how the locations of the goal and ball constrain the pattern-forming dynamics of attacker-defender dyadic systems. Ten high-level futsal matches were filmed and 13 goal sequences selected for analysis. Displacements of the players and the ball were filmed and digitized from 52 attacker-defender dyadic system interactions. Results showed that, although attackers and defenders exhibited similar angular orientations to the goal, the latter always remained closer to the goal than attackers. Observations revealed that in-phase patterns of coordination emerged from changes to both the distances and angles of attackers and defenders to the goal. Attackers always remained closer to the ball than defenders, while the latter exhibited a lower angle to the ball than attackers. A pattern of in-phase coordination modes emerged between the attackers and defenders' distances and angles to the ball. This study helps us to understand interpersonal interactions in team sports by explaining how attackers and defenders use information about their relative positioning to the goal and the ball to perform successfully.